The possibility of applying ABC system in service companies: Application study in Dar A’salam Bank Diwaniyah department (Journal of Accounting and Financial Studies ( JAFS ), 2011)
The studies in ABC system have become so many nowadays especially in industrial companies. But they are almost rare in service companies and that has put more difficulties in front of the researcher.This study consists of two sides, theoretical and practical. The first side (theoretical) deals with the most important features of ABC system and it focuses on its characteristics, standards and aims. While the practical side deals with the practice of this system in one of these service companies which is Dar-A’Salam Bank. The researcher has made use of being the accounting adviser of the bank and that he can get the necessary data. He has come up with, after making a comparison between the cost of ABC system and traditional cost system, that justice is not achieved according to the traditional system and the method followed is unfair. So the researcher has recommends to follow ABC system since it supplies us with more accurate and detailed financial and non-financial information.Cost accounting has suffered from big troubles in the second half of the nineteen century when the investment in fixed assets increased greatly. As a result there was a need for active cost system to distribute the cost related to these assets, and if it is easy to distribute direct cost, it is very difficult to distribute indirect cost and we may consider this the big problem.  There were many studies about this problem. Among these studies those done by “Arther L. Thomas” such as “Problem of distribution in financial accounting theory”, “The Useful Random distribution” and his last study “The Problem of distribution” in 1974 in which he insisted that distribution process is unjustified logically”. In that it is destruction for distribution process as a system and logic. Thomas theory was not accepted, therefore, there was Zimmer man’s study “Comparison of cost and benefit of distribution Process” 1979, which was considered a better study and a better defense for the distribution process.The researchers divided into supporters, objectors and independents. This argument helped to develop distribution process through cost accounting. Indirect cost began to cause a trouble in the shade of technological development in product. So the traditional methods were not sufficient in giving accurate output and not enough to make a strategic and managing decision. Therefore, there was a need for a new system, which can give the theoretical justification described by Thomas. This system should also be accepted by the practicians and able to solve distribution troubles.ABC system was a result of these studies and researches which the researchers insisted that it was the best solution.